Answer:
A
Step-by-step explanation:
The correct answer will be A
Have a great day
We have this equation:
![P=2L+2W](https://tex.z-dn.net/?f=P%3D2L%2B2W)
So, we need to solve this equation for L. Then we sum -2W in each member of the equation, like this:
![P-2W=2L+2W-2W](https://tex.z-dn.net/?f=P-2W%3D2L%2B2W-2W)
![P-2W=2L](https://tex.z-dn.net/?f=P-2W%3D2L)
Then, dividing the equation by 2:
![\frac{P-2W}{2}=L](https://tex.z-dn.net/?f=%5Cfrac%7BP-2W%7D%7B2%7D%3DL)
Finally, let's order this equation:
Answer:
43. ![= \frac{.0045}{100}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B.0045%7D%7B100%7D)
44.
45. 8
Step-by-step explanation:
43. 0.45% = .0045
![= \frac{.0045}{100}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B.0045%7D%7B100%7D)
44.
• ![9\frac{4}{5}](https://tex.z-dn.net/?f=9%5Cfrac%7B4%7D%7B5%7D)
=
45. VIII = 8
Answer:
3x +4y = 118
5x+6y =180
y= $25
Step-by-step explanation:
Let x = the cost of a flashlight
Let y = the cost of a sleeping bag
3x +4y = 118
5x+6y =180
Multiply the first equation by -5
-5(3x +4y) = -5*118
-15x -20y = -590
Multiply the second equation by 3
3(5x+6y) =3*180
15x + 18y = 540
Add the modified equations together.
We are using elimination to eliminate the variable x
-15x -20y = -590
15x + 18y = 540
----------------------------
-2y = -50
Divide by -2
-2y/-2 = -50/-2
y =25
Each sleeping bag costs $25
C is the answer...............................